Students’ Ability in Using Gerund: Kemampuan Siswa dalam Menggunakan Gerund - Iklimah, Iklimah; Istiqomah Aprimargani Muliayu Ningsih; Heri Pranata (LPPM Institut Studi Islam Sunan Doe, 2023)
In learning English as a foreign language, it has an often been found that Indonesian students still have some difficulties. Not only in reading, writing, listening and speaking but also in the file of structure as well. English has a consistent structure. In learning English structure still found that the students have some difficulties in learning them.The objective of this study is to investigate the students’ ability in using gerund. This research method employed a descriptive qualitative method. The instrument used in this study was test. The participants of this study were the second-year students of MA Mu’allimin NWDI Pancor. After analysing the data, the researcher was found some students ability in using gerund like gerund as the subject, gerund as the complement, and gerund after preposition. Based on the data gained, the researcher was found that the maximum score was 19 and the minimum score was 8. While the mean was 12,7. The result and discussion will be further presented